The Influence of Promotion, Price, and Store Atmosphere on Consumer Purchase Interest at TB. Barokah Mulya Dumpi Lamongan - Noviana Rismaniyah; Moh. Muklis Sulaeman; Diah Ayu Novitasari; Nanto Purnomo (Research Trend in Technology and Management, 2024)
Indonesia is a country that experiences an increase in population growth rate every year, along with the increasing population, the development of existing infrastructure, including residential areas, also increases. This study aims to determine the effect of promotion, price, and store atmosphere on purchasing interest at TB. Barokah Mulya Dumpi Lamongan. This study uses a quantitative method. The population in this study were consumers of TB. Barokah Mulya Dumpi Lamongan. Sampling in this study was based on the solvin research formula which obtained 147 samples. Testing in this study used analytical tools of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, coefficient of determination test, t test, and f test. The results of the study showed that Promotion had a significant effect on consumer purchasing interest, Price had a significant effect on consumer purchasing interest, Store Atmosphere had a significant effect on consumer purchasing interest, and the three variables had a simultaneous effect on Consumer Purchasing Interest.